2013
DOI: 10.1002/uog.12488
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal translucency and major congenital heart defects in fetuses with normal karyotype: a meta‐analysis

Abstract: Objective To pool published data regarding the sensitivity and specificity of nuchal translucency (NT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 40 publications
3
54
1
8
Order By: Relevance
“…1,4,13,14 To our knowledge, this article is the first practical description of a straightforward and direct screening method for congenital heart defects in the first trimester. In this study we found that our simple firsttrimester cardiac protocol was an effective screening method for congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,13,14 To our knowledge, this article is the first practical description of a straightforward and direct screening method for congenital heart defects in the first trimester. In this study we found that our simple firsttrimester cardiac protocol was an effective screening method for congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged NT may be present in cases of chromosomal pathologies [Kagan et al, 2008] as well as cardiac anomalies [Hyett et al, 1996;Sotiriadis et al, 2013] and certain genetic syndromes, especially Noonan syndrome [Pergament et al, 2011]. In 2009, Li and McDonald noted increased NT in the first-trimester scan of the fetus, which later was diagnosed with SGB syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…International Society of Ultrasound in Obstetrics and Gynecology anbefaler i sine siste retningslinjer fra mars 2013 bruk av fargedoppler ved ultralydundersøkelsen av fosterhjertet (11). Studier viser at ultralydundersøkelse rundt uke 12 i svangerskapet har potensial til å påvise opp mot 45 % av alvorlige hjertefeil hos foster med normale kromosomer og nakkeoppklaring over 95-prosentilen (12).…”
Section: Prenatal Diagnostikkunclassified